2020
DOI: 10.1016/j.jdeveco.2020.102441
|View full text |Cite
|
Sign up to set email alerts
|

The Belt and Road Initiative: Reshaping economic geography in Central Asia?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The simulation results showed that globalized public policies could promote the convergence of income disparity in the long run (Boucekkine et al, 2013 ), and many empirical studies have also found that public policy changes can explain income disparity to a large extent (Cai, 2007 ; Celeste and Nadanovsky, 2010 ). However, in the research on the globalized public policy of the BRI, some studies believed that the BRI led to a greater concentration of economic activities in some regions, especially in the BRI economies, so benefits from the BRI will not be shared equally, resulting in a widening regional income disparity (Enderwick, 2018 ; Bird et al, 2020 ), which is inconsistent with the findings of this paper and may weaken the research conclusions of this paper to a certain extent. This is mainly because the samples of these two studies are different from this paper, which can lead to different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation results showed that globalized public policies could promote the convergence of income disparity in the long run (Boucekkine et al, 2013 ), and many empirical studies have also found that public policy changes can explain income disparity to a large extent (Cai, 2007 ; Celeste and Nadanovsky, 2010 ). However, in the research on the globalized public policy of the BRI, some studies believed that the BRI led to a greater concentration of economic activities in some regions, especially in the BRI economies, so benefits from the BRI will not be shared equally, resulting in a widening regional income disparity (Enderwick, 2018 ; Bird et al, 2020 ), which is inconsistent with the findings of this paper and may weaken the research conclusions of this paper to a certain extent. This is mainly because the samples of these two studies are different from this paper, which can lead to different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of the Central Asian countries (multi-country) literature on the Granger causality (Granger, 1969) and VAR methodology (Sims, 1972) that plethora of survey around (Ashurov et al, 2020;Batsaikhan and Marek, 2017;Bird et al, 2020;Nurseiit, 2020;Rosenbaum et al, 2012). For example, Ashurov et al, (2020) investigated and identified the determinants of foreign direct investment (FDI) in the Central Asian countries, specifically Tajikistan, Kazakhstan, Kyrgyzstan, Turkmenistan, and Uzbekistan, between 2000 to 2017.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Belt and Road Initiative has created an extensive transportation infrastructure, decreased transportation costs, accelerated transportation efficiency, and provided a prominent opportunity for economic growth. Despite some reports indicate that the total actual income generated by the Belt and Road Initiative is less than 2% of regional income (Bird et al, 2020), the improvement in infrastructure will contribute to an increase in employment and a concentration of economic activity, which can further boost income. However, the connectivity of transportation facilities has inevitably led to an unprecedented increase in carbon emissions from transportation that could trap the country or region in an unsustainable development cycle lasting several decades (Solaymani, 2019).…”
Section: Introductionmentioning
confidence: 99%